A SURVEY OF ANTIBIOTICS PURCHASED WITHOUT PRESCRIPTION AMONG NON-HEALTH SCIENCE STUDENTS IN JEMBER, INDONESIA - Antonius Nugraha Widhi Pratama; Anis Rohmawati; Ema Rachmawati (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2018)
Previous research showed that self-medication practice with antibiotics is widespread in developing countries and tertiary students are among these consumers. This study aimed to estimate the prevalence of the use of antibiotics without prescription among non-health science students in Jember and to identify the sources of non-prescription antibiotics. This cross-sectional survey was conducted between April and June 2016 in all non-health science faculties of Universitas Jember. A questionnaire containing four main short questions about antibiotics use and questions related to socio-demographic information was distributed to students who gave consent. A number of 130 (58.5%) respondents admitted to ever acquire antibiotics without the presence of a physician prescription. Self-medication with antibiotics tended to be done by students from rural areas (p=0.04) and without health insurance (p=0.04). The sources of non-prescription antibiotics vary, but pharmacy was the most frequently cited to be the source (n=82; 46.3%). This study showed that the use of antibiotics without prescription among non-health science students and the sale of antibiotics without prescription among pharmacies in Jember are prevalent. Real responses from the government, relevant health professional associations, and education institutions to intervene these problems are significantly needed.